STRATEGI PENGEMBANGAN KUALIFIKASI DAN KOMPETENSI GURU (Menurut Undang-Undang Guru & Dosen dan Standar Nasional Pendidikan) - Sunhaji Sunhaji (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2012)
Abstract : Teacher is a means of shaping human resources in nation development, especially in the areas of education. Teacher is the giver of inspiration, driver, and coaches in the mastery of certain skills to others, especially for the students to prepare them to build lives and their social environment. It is an undoubtable that the more qualified teachers, the greater contribution to the development of their students and the development community itself. More fundamental quality of teachers is also actively seeking progress in the improvement of skills in work and in social service. Key Words: Teachers, Qualified, and Competent.